"There were more decisions and more options than just yes or no": Evaluating a decision aid for advanced cancer patients and their family caregivers. Issue 1 (12th August 2016) - Bakitas, Marie; Dionne-Odom, J. Nicholas; Jackson, Lisa; Frost, Jennifer; Bishop, Margaret F.; Li, Zhongze
Abstract: Objective: Few decision aids are available for patients with a serious illness who face many treatment and end-of-life decisions. We evaluated the Looking Ahead: Choices for Medical Care When You're Seriously Ill ® patient decision aid (PtDA), one component of an early palliative care clinical trial. Method: Our participants included individuals with advanced cancer and their caregivers who had participated in the ENABLE (Educate, Nurture, Advise, Before Life Ends) early palliative care telehealth randomized controlled trial (RCT) conducted in a National Cancer Institute-designated cancer center, a U.S. Department of Veterans Affairs medical center, and affiliated outreach clinics in rural New England. ENABLE included six weekly patient and three weekly family caregiver structured sessions. Participants watched the Looking Ahead PtDA prior to session 3, which covered content on decision making and advance care planning. Nurse coaches employed semistructured interviews to obtain feedback from consecutive patient and caregiver participants approximately one week after viewing the Looking Ahead PtDA program (booklet and DVD). Results: Between April 1, 2011, and October 31, 2012, 57 patients (mean age = 64), 42% of whom had lung and 23% gastrointestinal cancer, and 20 caregivers (mean age = 59), 80% of whom were spouses, completed the PtDA evaluation. Participants reported a high degree of satisfaction with the PtDA format, as well as with its length and clarity. They found the format of using patient interviews "validating." The key themes were: (1) "the earlier the better" to view the PtDA; (2) feeling empowered, aware of different options, and an urgency to participate in advance care planning. Significance of results: The Looking Ahead PtDA was well received and helped patients with a serious illness realize the importance of prospective decision making in guiding their treatment pathways. We found that this PtDA can help seriously ill patients prior to the end of life to understand and discuss future healthcare decision making. However, systems to routinely provide PtDAs to seriously ill patients are yet not well developed.